2021
DOI: 10.1002/jum.15886
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Contrast‐Enhanced Ultrasound Characteristics and Molecular Subtypes of Breast Cancer

Abstract: Objective This study aimed to investigate the correlation between contrast‐enhanced ultrasound (CEUS) features and molecular subtypes of breast cancer (BC). Methods A total of 116 patients (116 lesions) with pathologically diagnosed BC who received conventional ultrasound and CEUS before surgery were enrolled in this study. BC molecular subtypes were identified by postoperative pathological and immunohistochemical analysis as Luminal A (LA), Luminal B (LB), HER2 (H2) over‐expression, and triple‐negative (TN). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…TNBC tumours in our study had a propensity to show oval shape with microlobulated and circumscribed margins. This finding is in agreement with previously conducted studies which also demonstrated oval shape with circumscribed margins as a feature of TNBC rather than the luminal epithelium subtype, which are often seen as irregular mass with angular and spiculated margins consequent to slow infiltration [ 12 , 13 , 21 , 22 ]. The smooth appearance has also been linked with the rapidity of tumour progression [ 15 , 23 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…TNBC tumours in our study had a propensity to show oval shape with microlobulated and circumscribed margins. This finding is in agreement with previously conducted studies which also demonstrated oval shape with circumscribed margins as a feature of TNBC rather than the luminal epithelium subtype, which are often seen as irregular mass with angular and spiculated margins consequent to slow infiltration [ 12 , 13 , 21 , 22 ]. The smooth appearance has also been linked with the rapidity of tumour progression [ 15 , 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…The prognosis of the TN subtype remains the worst and chemotherapy forms the mainstay of treatment for this subtype [ 19 ]. This heterogeneous behaviour of breast cancer has prompted studies regarding the parameters which may potentially allow differentiation of the various subtypes from each other in recent years [ 13 , 15 , 16 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results concur with those of Wen B et al. ( 24 ) in that HER-2 overexpressed and triple-negative breast lesions can secrete more vascular endothelial growth factor, leading to higher angiogenesis and vascular permeability and significant hyper-perfusion situation in the tumors.…”
Section: Discussionsupporting
confidence: 93%
“…The qualitative CEUS features were evaluated according to the literatures, 15–17 including: (1) shape after enhancement (regular, irregular); (2) margin after enhancement (clear, unclear); (3) enhanced homogeneity (homogeneous, heterogeneous); (4) perfusion defect (absent, present); (5) enhanced direction (diffuse, centripetal, centrifugal); and (6) nourishing vessels (absent, present).…”
Section: Methodsmentioning
confidence: 99%
“…Tumor shape, margin, echo pattern, orientation, posterior features, echogenic rim, and micro-calcification were assessed according to the ACR BI-RADS Atlas 5th edition ultrasound lexicon. 14 The qualitative CEUS features were evaluated according to the literatures, [15][16][17] including: (1) shape after enhancement (regular, irregular); (2) margin after enhancement (clear, unclear); (3) enhanced homogeneity (homogeneous, heterogeneous); (4) perfusion defect (absent, present); (5) enhanced direction (diffuse, centripetal, centrifugal); and (6) nourishing vessels (absent, present).…”
Section: Gray Scale Ultrasound and Ceus Analysismentioning
confidence: 99%